No Free Lunch With Herbal Preparations: Lessons From a Case of Parkinsonism and Depression Due to Herbal Medicine Containing Reserpine - Rijntjes, Michel; Meyer, Philipp T. (Frontiers in Neurology, 2019)
The increasing use of herbal medicines calls for a heightened awareness of their potential side-effects. This especially pertains to western countries, where patients tend to use herbal medicine as self-medication, often alongside regular prescriptions, and physicians have less experience with their application. Here we report a case in which Parkinsonism, depression, and an atypical finding detected by dopamine transporter single-photon emission computed tomography were all belatedly recognized as side-effects of herbal medicine. This only occurred because one of its active ingredients, reserpine, has been extensively studied. For most other herbal medicines, however, knowledge about side-effects remains scarce or unavailable. Therefore, we suggest that physicians, when taking a medication history, should actively ask for the use of any herbal preparations.